The financing of higher education in latin america: a case analysis 1990-2008 (2011)
The Latin American university develops itself among big tensions and contradictions arising from the implementation of the Consensus of Washington and the demands of financial resources for the University to carry on its missionary duty as well. Great tensions between the followers of some managerial collegiate practices, proper of the nineteenth century universities, and the needs for a rational management of institutions of high organizational complexity, such as the large Latin American universities at the onset of the XXI century, also arise. This article discusses these problems and analyzes their repercussions.